2018
DOI: 10.3892/ijmm.2018.4005
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 protects against H2O2‑induced neuronal damage due to inhibition of the NLRP1 inflammasome signalling pathway in hippocampal neurons in�vitro

Abstract: Oxidative stress and neuroinflammation are important in the pathogenesis of ageing and age-related neurodegenerative diseases, including Alzheimer’s disease. NADPH oxidase 2 (NOX2) is a major source of reactive oxygen species (ROS) in the brain. The nucleotide-binding oligomerisation domain (NOD)-like receptor protein 1 (NLRP1) inflammasome is responsible for the formation of pro-inflammatory molecules in neurons. Whether the NOX2-NLRP1 inflammasome signalling pathway is involved in neuronal ageing and age-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“… 24 , 25 Chronic glucocorticoid exposure significantly activated NLRP1 inflammasome in hippocampal neurons, thus to increase neuron-inflammation. 28 Ginsenoside Rg1 protected against neuronal degeneration by inhibiting NLRP1 inflammasome both in H 2 O 2 -treated hippocampal neurons in vitro 9 and in dexamethasone-treated mice. 29 NLRP1 inflammasome activation was proved to result in pyroptosis, a caspase-1-dependent inflammatory form of cell death that is distinct from apoptosis or other cell death mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 25 Chronic glucocorticoid exposure significantly activated NLRP1 inflammasome in hippocampal neurons, thus to increase neuron-inflammation. 28 Ginsenoside Rg1 protected against neuronal degeneration by inhibiting NLRP1 inflammasome both in H 2 O 2 -treated hippocampal neurons in vitro 9 and in dexamethasone-treated mice. 29 NLRP1 inflammasome activation was proved to result in pyroptosis, a caspase-1-dependent inflammatory form of cell death that is distinct from apoptosis or other cell death mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Xu et al reported that Ginsenoside Rg1 protect against H 2 O 2 -induced neuronal damage by inhibiting the activation of NLRP1 inflammasome in hippocampal neurons in vitro. 9 These findings suggested that the strategies targeting NLRP1 inflammasome activation might be useful in the therapy of AD.…”
Section: Introductionmentioning
confidence: 97%
“…Ginsenoside Rg1 (Rg1) is a bioactive component in ginseng, which has been used to delay senescence since ancient times. Our previous studies suggested that Rg1 could ameliorate H 2 O 2 -induced hippocampal neuron damage in vitro [12]. The APP/PS1 transgenic mouse is the most commonly used AD model animal, which exhibits obvious elevation of Aβ deposition and behavioral abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research indicated that the expressions of NOX2 and its subunits of Rac1, p47phox and p22phox were signi cantly increased in long-term cultured hippocampal neurons [17]. Meanwhile, treatment with Rg1 signi cantly decreased the expressions of NOX2 and p47phox in H 2 O 2 -induced hippocampal neurons [12]. Therefore, we speculated that Rg1 treatment might inhibit NOX2-mediated neuronal oxidative stress and neuroin ammation in APP/PS1 AD mice.…”
mentioning
confidence: 92%
See 1 more Smart Citation